Smart sensory home technology with bluetooth module / Amar Muqri Hairul Arifin - Hairul Arifin, Amar Muqri (2024)
Through these creative studies the conventional switches that have served us for decades are being reinterpreted in the constantly changing world of home automation. The main goal of this research is to design an effective automated switch system for home appliances that allows users to operate them with their cell phones by using the power of current technology, namely a Bluetooth module. With the integration of sensor-based processes into our houses, this initiative advances our understanding of everyday routines in a ground-breaking way. We have the potential to completely transform the way we interact with our appliances by creating a self-running smart home system that is built on Bluetooth and runs on the Thinker Cad and Proteus platforms. There are many benefits to this technology. Just think about how convenient it would be if your fans, TV, and lights in your house automatically turned on as you walked in the door and acted in unison with your movements. An array of sensors that can identify human presence inside a certain area is at the center of this system. When a sensor detects the presence of an individual, it quickly connects with a Bluetooth module, which then sends the information to your smartphone so that it can be easily accessed. This prototype is capable of detecting human movements with the use of Arduino programming. Thanks to this cutting-edge advancement in home automation, people may explore their houses without giving switching a second thought and can easily and comfortably integrate into their regular routines. Traditional switches, which have been used for decades, are being reinterpreted in the ever-changing field of home automation thanks to creative studies. The goal of this study is to create an efficient automated switch system for home appliances that allows users to control them with their cellphones by using the capabilities of current technology, specifically a Bluetooth module. The incorporation of sensor-based processes into our houses represents a paradigm shift in our view of daily activities. The envisioned self functioning smart home system, built on Bluetooth and running on the Thinker Cad and Proteus platforms, has the potential to transform our interactions